Computer-assisted image analysis protocol that quantitatively measures subnuclear protein organization in cell populations - Ty C. Voss; Ignacio A. Demarco; Cynthia F. Booker; Richard N. Day (BioTechniques)
Many nuclear proteins, including the nuclear receptor co-repressor (NCoR) protein are localized to specific regions of the cell nucleus, and this subnuclear positioning is preserved when NCoR is expressed in cells as a fusion to a fluorescent protein (FP). To determine how specific factors may influence the subnuclear organization of NCoR requires an unbiased approach to the selection of cells for image analysis. Here, we use the co-expression of the monomeric red FP (mRFP) to select cells that also express NCoR labeled with yellow FP (YFP). The transfected cells are selected for imaging based on the diffuse cellular mRFP signal without prior knowledge of the subnuclear organization of the co-expressed YFP-NCoR. The images acquired of the expressed FPs are then analyzed using an automated image analysis protocol that identifies regions of interest (ROIs) using a set of empirically determined rules. The relative expression levels of both fluorescent proteins are estimated, and YFP-NCoR subnuclear organization is quantified based on the mean focal body size and relative intensity. The selected ROIs are tagged with an identifier and annotated with the acquired data. This integrated image analysis protocol is an unbiased method for the precise and consistent measurement of thousands of ROIs from hundreds of individual cells in the population.